PENGARUH KINERJA KEUANGAN DAN KEBIJAKAN DEVIDEN TERHADAP HARGA SAHAM - Arief, Salamun; Angraini, Dila (Politeknik Negeri Ambon, 2025)
Introduction: This study examines the impact of financial performance and dividend policy on stock prices.Methods: A quantitative research approach is applied, utilising secondary data. The sampling method employed is purposive sampling. The research sample includes 48 real estate and property companies listed on the Indonesia Stock Exchange during the period of 2018 to 2023. Data processing and analysis are conducted using EViews version 9 with a regression analysis method. Results: The findings reveal that both financial performance and dividend policy significantly influence stock prices, both jointly and individually. Keywords: Financial Performance, Dividend Policy, Stock Price